Factors associated with glycaemic control among diabetes mellitus type 2 patients attending health clinics in Tampin district Negeri Sembilan, Malaysia - Wan Hamdzan, Wan Farzana Fasya (2016)
Introduction: Diabetes Mellitus Type 2 has become one of the most serious global health problems nowadays. The prevalence of Diabetes Mellitus Type 2 in Malaysia has increased to 31.0% in 5 years, from 11.6% in 2006 to 15.2% in 2011. In 2012, the Malaysian National Diabetes Registry reported that 76.2% of the proportion are having poor glycaemic control (HbA1c ≥6.5%) and only 23.8% are having good glycaemic control (HbA1c <6.5%). Objective: The aims of this study are to determine the factors associated with poor glycaemic control among Diabetes Mellitus Type 2 patients attending health clinics in Tampin District, Negeri Sembilan,Malaysia Method: A cross sectional study was conducted among 324 patients with Diabetes Mellitus Type 2 in July 2013 – January 2014 in all 5 health clinics in Tampin district, Negeri Sembilan by using proportionate stratified random sampling and stratified random sampling. Data collection was done through face to face interviews using structured validated questionnaires. Data were analysed using Statistical Packages for Social Sciences version 22. Results: Response rate was 92%.The percentage of poor glycaemic control was 66.4%. Glycaemic control were found significantly associated with age (χ²=10.405, p=0.006), marital status (χ ²=5.718, p=0.017) education status (χ²=7.312, p=0.026), types of medication (χ²=18.058, p<0.001), family history of Diabetes Mellitus Type 2 (χ²=7.234, p=0.007), Co-morbidities (χ²=5.718, p=0.017), systolic blood pressure (χ²=18.515, p<0.001), diastolic blood pressure(χ²=9.574, p= 0.002), level of knowledge (χ²=23.209, p<0.001), types of foods containing fat that controlled by respondents (χ²=7.796 ,p=0.005), daily dietary intake of protein sources (χ²=19.173,p<0.001), self- monitoring blood glucose practice (χ²=16.935, p<0.001), taking medication other place than health clinics (χ²=5.907,p= 0.020),compliance of medication intake and appointment keeping with doctors (χ²=11.225, p=0.001), and level of physical activity (χ²=25.530, p=<0.001). In the multivariate model, those who were on insulin alone/combination of insulin and oral medication (AOR 3.217, 95% CI: 1.636, 6.327), co-morbidities (AOR 3.810, 95% CI: 1.507, 9.633), systolic blood pressure more than or equal than130mmHg (AOR 4.595, 95%CI: 2.328, 9.069), poor knowledge (AOR 3.927, 95% CI: 1.724, 8.944), dietary intake of protein sources (AOR 3.423, 95%CI: 1.707, 6.864), take foods that contain fat (AOR 3.116, 95% CI: 1.056, 9.193), not comply with medication intake and appointment with doctors (AOR 3.850, 95% CI: 1.497, 9.905), and inadequate level of physical activity (AOR 4.001, 95% CI: 1.649, 9.711) were significantly associated with poor glycaemic control. Conclusion: More than half (66.4%) of the respondents was having poor glycaemic control. Respondent who on insulin alone or combine medication, poor knowledge level, respondent who not controlling food containing fat, inadequate of physical activity and not comply with medication intake should be targeted with additional intervention to achieve optimal glycaemic control and boost healthy living.